2010
DOI: 10.1136/emj.2009.079160
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of frequent attenders of emergency department at an acute general hospital in Singapore

Abstract: With the ageing population and their complex healthcare needs, elderly patients with chronic medical conditions are expected to make up an increasing proportion of the workload of ED in the future. A systems approach and a disease and case management approach in collaboration with primary care providers are interventions recommended to stem this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 17 publications
7
40
1
Order By: Relevance
“…25 However, they employed a different definition for frequent attenders (five or more visits over a 12-month period) and performed a univariate analysis with a different outcome of interest (ED reattendance, defined as the second visit at the ED for any diagnosis within 12 months after the initial visit). Our study results were found to agree in general, but in addition our study attempted to differentiate between appropriate and inappropriate visits and the true costs that are associated with these visits.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, they employed a different definition for frequent attenders (five or more visits over a 12-month period) and performed a univariate analysis with a different outcome of interest (ED reattendance, defined as the second visit at the ED for any diagnosis within 12 months after the initial visit). Our study results were found to agree in general, but in addition our study attempted to differentiate between appropriate and inappropriate visits and the true costs that are associated with these visits.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent use of hospital emergency departments (EDs) by specific patient subgroups has been reported in several countries, irrespective of the details of the health care system in use. [1][2][3][4][5][6][7][8] Frequent users are patients who use EDs on multiple occasions. Definitions and visit number thresholds vary across studies; according to Locker et al, 9 a frequency of more than 4 attendances per year corresponds to nonrandom events, and use of this threshold may improve comparisons between studies.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific literature suggests that demand for emergency department services has been increasing over recent decades in many geographic jurisdictions, including: Singapore [2], Spain [3] and the United States [4]. Changing preferences of medical consumers may be related to this increased demand for emergency health services.…”
Section: Introductionmentioning
confidence: 99%